Can I rely on you? - Billur Aksoy; Catherine C. Eckel; Rick K. Wilson (Games, 2018)
This paper introduces a strategic element into the dictator game by allowing recipients to select their dictator. Recipients are presented with the photographs of two dictators and the envelopes containing their allocations, and are then asked to select which dictator's gift they would like to receive. The recipient is paid the contents of the envelope they select. The photographs carry information about the gender and race/ethnicity of the dictators, and we ask an independent sample of raters to evaluate the photographs for other characteristics. While gender and ethnicity do not affect the recipient's choice, one characteristic inferred from the photos makes them significantly more likely to be selected: Their perceived reliability.
Keywords: 330; dictator game; lab experiment; generosity; face evaluation